MyD88-mediated innate sensing by oral epithelial cells controls periodontal inflammation. (March 2018) - Delitto, Andrea E.; Rocha, Fernanda; Decker, Ann M.; Amador, Byron; Sorenson, Heather L.; Wallet, Shannon M.
Highlights: Loss of oral epithelial cell MyD88 expression results in exacerbated induced bone loss. Loss of oral epithelial cell MyD88 expression results in induced tissue inflammation. Loss of oral epithelial cell MyD88 expression results in uninduced tissue inflammation. Loss of oral epithelial cell MyD88 expression results in uninduced bone loss. Oral epithelial cell MyD88-dependent signaling regulates immunological balance. Abstract: Periodontal diseases are a class of non-resolving inflammatory diseases, initiated by a pathogenic subgingival biofilm, in a susceptible host, which if left untreated can result in soft and hard tissue destruction. Oral epithelial cells are the first line of defense against microbial infection within the oral cavity, whereby they can sense the environment through innate immune receptors including toll-like receptors (TLRs). Therefore, oral epithelial cells directly and indirectly contribute to mucosal homeostasis and inflammation, and disruption of this homeostasis or over-activation of innate immunity can result in initiation and/or exacerbation of localized inflammation as observed in periodontal diseases. Dynamics of TLR signaling outcomes are attributable to several factors including the cell type on which it engaged. Indeed, our previously published data indicates that oral epithelial cells respond in a unique manner when compared to canonical immune cells stimulated in a similar fashion. Thus, the objective of this study was to evaluate the role of oral epithelial cell innate sensing on periodontal disease, using a murine poly-microbial model in an epithelial cell specific knockout of the key TLR-signaling molecule MyD88 (B6 K5Cre.MyD88plox ). Following knockdown of MyD88 in the oral epithelium, mice were infected with Porphorymonas gingivalis and Aggregatibacter actinomycetemcomitans by oral lavage 4 times per week, every other week for 6 weeks. Loss of oral epithelial cell MyD88 expression resulted in exacerbated bone loss, soft tissue morphological changes, soft tissue infiltration, and soft tissue inflammation following polymicrobial oral infection. Most interestingly while less robust, loss of oral epithelial cell MyD88 also resulted in mild but statistically significant soft tissue inflammation and bone loss even in the absence of a polymicrobial infection. Together these data demonstrate that oral epithelial cell MyD88-dependent TLR signaling regulates the immunological balance within the oral cavity under conditions of health and disease.